Contributing factors to will adoption among Muslim Community in Kota Bharu, Kelantan / Nur Syakirin Azman - Azman, Nur Syakirin (Faculty of Business and Management, 2019)
A will is a financial management instrument that will take effect after one's death. When a person died, their assets and property will be distributed to their heirs. Most of the Malaysian citizens were aware with the words of Islamic will but most of them did not practise it in their life. Will or wasiyyah should be practised in their daily lives so that they can prevent the dispute that may arise among the beneficiaries m future. Nowadays, there are about RM 60 billion of the assets and property that still have a problem regarding its status. It is because the beneficiaries did not able to claim the assets and property and it will lead to frozen estate. Due to that problem, this study has been conducted to investigate the contributing factors to will adoption among Muslim community since the amount of frozen estate and unclaimed property and assets are so high. This study adopts a qualitative research and the raw data can be described using descriptive analysis, correlation analysis, and multiple linear regressions. The data had been collected by distributing the questionnaire to the respondents. The dependent variable that had been used in this study is will adoption meanwhile independent variables are knowledge, religiosity, financial obligations and attitude. The data will be regress by Statistical Procedure of Social System (SPSS). This research will determine the factors that will contribute to the practise of will adoption.